Striking A Balance Between Legal Certainty, Justice And Utility To End The Clash Between Bankruptcy And Criminal Proceedings In Court Decision No. 11/Pdt.Sus-Gugatan Lain-lain/2018/PN.Jkt.Pst and No. 3 K/Pdt.Sus-Pailit/2019 - Nelson, Febby Mutiara; Sondang, Esther Melinia (Faculty of Law, Universitas Negeri Semarang, 2021)
The clash between bankruptcy and criminal proceedings is one of the obstacles which has been long faced by law enforcement officials. One of many examples of the intersection of the two proceedings is the case between the Bankruptcy Trustees of KSP Pandawa Mandiri Group dan Nuryanto with Depok District Attorneys. The case caused issues with the confiscated assets that were the objects in the bankruptcy and criminal court decisions. It stemmed from the conflict between provisions in Indonesian Bankruptcy Act and Criminal Procedure Code. This Note was conducted to analyze the judges' judicial decision-making concerning the three aspects of legal certainty, justice and utility as one way to resolve the conflict of norms. Generally, the Commercial Court and Supreme Court decisions have complied with the regulations of the prevailing laws and legal principles. However, the judgments are still not comprehensive and not quite right in the decisions. The Panel of Judges should not only stick on the legal certainty aspect but also the justice and utility aspects. Concerning the three aspects, the bankruptcy assets in the case should be handed over to the Bankruptcy Trustees.